Crop rotation method of slope cropland - REN YING; DOU JINGANG; XU CHEN; REN YANHUI; ZHAO HONGXIANG; XU CHANGHONG; TAN GUOBO; WANG BAOGUI; WANG XIAOHUI; MA WEI; MENG XIANGMENG; LI SUQIN; et al. (2017)
The invention discloses a crop rotation method of a slope cropland. The crop rotation method comprises the following steps of: before crop rotation, performing two-year crop rotation planting according to the planting sequences of spring buckwheat, sesame, wheat, cotton and autumn buckwheat after soil preparation, ridge consolidation, deep ploughing to remove grass and fertilization of the slope cropland in light of photo-thermal conditions of soil quality of the slope cropland; and before planting, separately performing airing, flatness removal and agent seed mixing on the crop seeds and performing planting management by combining a conventional planting management method of the crops and the sit situation of the planting slope cropland. By performing two-year crop rotation planting on the slope cropland according to the reasonable planting sequences of spring buckwheat, sesame, wheat, cotton and autumn buckwheat, the utilization ratio of water of soil is effectively increased, and the fertility and water re